2020
DOI: 10.1111/pan.13947
|View full text |Cite
|
Sign up to set email alerts
|

Response to: Biphasic cuirass model

Abstract: We would like to bring your attention to another mode of ventilation-the Biphasic Cuirass Ventilation (BCV) model which has many advantages in the pediatric population. BCV relies on a plastic cuirass shell (available in sizes from neonates to adult) connected to a ventilator which produces negative pressure on the thorax allowing air to rush in through the nose and mouth and into the lungs-release of the negative pressure allows passive exhalation (positive pressure can also be utilized to gently "push" the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We read with great interest the paper "Accuracy of dynamic preload variables for predicting fluid responsiveness in patients with pediatric liver cirrhosis: A prospective study" by Chen et al 1 In our opinion, there is another reason for the low prognostic value of dynamic parameters to predict fluid responsiveness (FR) in their study. The children were mechanically ventilated with tidal volume of 8 mL/kg, lower than the 10 mL/kg protocols used in earlier comparable studies, [2][3][4] and currently a lung protective strategy with smaller tidal volume is preferred by some or most anesthesiologists in clinical practice. Furthermore, they used positive end expiratory pressures (PEEP) of 5 cm H 2 O.…”
Section: Dynamic Preload Variables To Predict Fluid Responsiveness Inmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the paper "Accuracy of dynamic preload variables for predicting fluid responsiveness in patients with pediatric liver cirrhosis: A prospective study" by Chen et al 1 In our opinion, there is another reason for the low prognostic value of dynamic parameters to predict fluid responsiveness (FR) in their study. The children were mechanically ventilated with tidal volume of 8 mL/kg, lower than the 10 mL/kg protocols used in earlier comparable studies, [2][3][4] and currently a lung protective strategy with smaller tidal volume is preferred by some or most anesthesiologists in clinical practice. Furthermore, they used positive end expiratory pressures (PEEP) of 5 cm H 2 O.…”
Section: Dynamic Preload Variables To Predict Fluid Responsiveness Inmentioning
confidence: 99%
“…Previous study demonstrated that diagnostic accuracy to predict FR decreases with the use of PEEP and smaller tidal volume. 4,5 The hypothesis that the accuracy of dynamic preload variables to predict FR is reduced in children with liver cirrhosis because they may have lower systemic vascular resistance and higher vascular compliance is reasonable, though their data demonstrated cardiac index and systemic vascular resistance were "comparable to the normal ranges in children without cirrhosis." So the accuracy of dynamic parameters to predict FR in children with typical hyperdynamic circulation remains unclear.…”
Section: Dynamic Preload Variables To Predict Fluid Responsiveness Inmentioning
confidence: 99%